Force enhancement of quadriceps femoris in vivo and its dependence on stretch-induced muscle architectural changes - Seiberl, W.; Hahn, D.; Kreuzpointner, F.; Schwirtz, A.; Gastmann, U. (Journal of Applied Biomechanics, 2010)
The purpose of this study was to investigate if force enhancement (FE) in vivo is influenced by stretch-induced changes of muscle architecture. Therefore, 18 subjects performed maximum voluntary isometric (100° knee flexion angle) and isometric-eccentric-isometric stretch contractions (80°-100°; omega = 60°?s-1) whereby pennation angle and fascicle length of vastus lateralis was determined using ultrasonography. We found significant (2-way repeated ANOVA; alpha = 0.05) enhanced torque of 5-10% after stretch as well as significant passive FE but no significant differences in muscle architecture between isometric and stretch contractions at final knee angle. Furthermore, EMG recordings during a follow-up study (n = 10) did not show significant differences in activation and mean frequency of contraction conditions. These results indicate that FE in vivo is not influenced by muscle architectural changes due to stretch.